A House Divided: the Murrays of the Border and the Rise and Decline of a Small Irish House. (13th July 2018) - Leary, Peter
Abstract: The thatched farmhouse in which the Murray family lived dated from at least the middle of the nineteenth century when James Fee, a grandfather of Mrs Murray, returned to Ireland from America with enough money to marry and settle down. Originally a public house it stood directly on the dividing line between County Fermanagh and County Cavan. The Government of Ireland Act, 1920 and the Anglo-Irish Treaty of 1921 elevated this unimportant boundary into a border between states. With one part in Northern Ireland (and, therefore, the United Kingdom) and another part in the Irish Free State, the Murrays could sit on a chair 'in the Six Counties' while eating off 'the table in the Twenty-six', or pass the salt back and forward from North to South. These humorous features of partition stood in contrast both to the family's modest circumstances and to the conflict, road closures and restrictions that shaped border life. In time, the house attracted the attention of propagandists, journalists and travel writers, and brought the Murrays into contact or, in the last instance, correspondence with politicians, foreign visitors, and the British monarch, Queen Elizabeth II. This paper concerns the remarkable story of this otherwise unremarkable family and their home.